The influence of academic buoyancy on academic stress: A case study at SMP “TV” - Renata Raissa Sondakh; Weny Savitry Pandia Sembiring (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2025)
This study aims to investigate the influence of academic buoyancy on the levels of academic stress among students. Adopting a quantitative design, this study involved 140 students at SMP (Middle School) “TV”, selected using a convenience sampling technique. The study employed the Student Stress Inventory and the Academic Buoyancy Scale for data collection, and the correlation and regression techniques for data analysis. Results showed a positive correlation between academic stress and students’ academic stress levels. Academic buoyancy plays a role in predicting middle school students’ levels of academic stress despite a small impact (R2 = 0.091). Further research is recommended to explore personal and demographic factors that contribute to academic buoyancy. Teachers and school counselors may need to promote students’ confidence and competence in overcoming academic challenges by building a positive climate at school and providing trainings for students